C-banding karyotypes of two species of Primnoa (Orthoptera: Catantopidae) from Northeast China - Ren, Bing-Zhong; Li, Na; Wei, Wen-Juan; Wang, Li-Ming (Zootaxa, 2008)
Chromosomes and C-banding karyotypes of Primnoa cavicerca Zhang and Primnoa mandshurica (Rme.), which were collected in Songhua Lake, Jilin Province, China, were studied for the first time. In the males, the chromosome numbers of these two species were found to be 2n (%) =23, with three pairs of large chromosomes, and X chromosomes are middle chromosomes. All chromosomes are telocentric. This genus has the basic Orthopteran sex determining mechanism XX&/ X0%. All the chromosomes possess centromeric C-bandings. The differences of these two species are also very remarkable, such as genome formula, terminal bandings, medial bandings and content of heterochromatin.